Assessing the circularity of regions: Stakes of trade of waste for treatment. (13th February 2021) - Towa, Edgar; Zeller, Vanessa; Achten, Wouter M. J.
Abstract: The degree of circularity of a region describes the proportion of materials recovered and reintroduced in that region of the total materials in that region. Quantifying the degree of circularity of a region is important, to prioritize and adequately implement circular economy (CE) strategies. Besides, regions may import and export waste treatment services. Efficient CE strategies should integrate the circularity embodied in the interregional linkages regarding waste treatment. However, the existing analyses of the degree of circularity of regions do not consider the trade of waste for treatment between regions. We fill this gap by proposing the trade‐corrected circularity index and trade‐corrected circularity gap index as two novel indicators, including their methodology and application for the case of Belgian regions. We used the multiregional physical supply and use the table we previously developed at the subnational Belgian level for 2011 and focused on Brussels, Flanders, and Wallonia. The results show that Brussels, Flanders, and Wallonia are 0%, 6.3%, and 8.1% circular, respectively, and when considering the trade of waste for treatment, they are 7.7%, 6%, and 8.5% circular, respectively. Further results include details of the circularity per type of materials (biomass, fossil fuels, metals, and non‐metallic minerals) as well as the circularity inherent to the trade of waste between regions. This paper ends with a discussion on the methodological and conceptual findings, the CE policy implications, and the contributions to the debate on measuring the circularity of regions when the trade of waste is at stake.